Amorphophallus coudercii (Araceae), a new record for Thailand - Promprom, Wilawan; Chatan, Wannachai (Thai Forest Bulletin (Botany), 2023)
Amorphophallus coudercii is reported as a new record from Nakhon Phanom Province, North-Eastern Thailand. The species is characterized by having a long tuber, a male floral zone contiguous to the female zone, the absence of an appendix, and the presence of warts on the adaxial side near the base of the spathe. Detailed descriptions based on recently collected plant materials, as well as notes on the distribution and ecology, and photographs are presented.